Experimental feasibility of multistatic holography for breast microwave radar image reconstruction. Issue 8 (19th July 2016) - Flores‐Tapia, Daniel; Rodriguez, Diego; Solis, Mario; Kopotun, Nikita; Latif, Saeed; Maizlish, Oleksandr; Fu, Lei; Gui, Yonsheng; Hu, Can‐Ming; Pistorius, Stephen
Abstract : Purpose: The goal of this study was to assess the experimental feasibility of circular multistatic holography, a novel breast microwave radar reconstruction approach, using experimental datasets recorded using a preclinical experimental setup. The performance of this approach was quantitatively evaluated by calculating the signal to clutter ratio (SCR), contrast to clutter ratio (CCR), tumor to fibroglandular response ratio (TFRR), spatial accuracy, and reconstruction time. Methods: Five datasets were recorded using synthetic phantoms with the dielectric properties of breast tissue in the 1–6 GHz range using a custom radar system developed by the authors. The datasets contained synthetic structures that mimic the dielectric properties of fibroglandular breast tissues. Four of these datasets the authors covered an 8 mm inclusion that emulated a tumor. A custom microwave radar system developed at the University of Manitoba was used to record the radar responses from the phantoms. The datasets were reconstructed using the proposed multistatic approach as well as with a monostatic holography approach that has been previously shown to yield the images with the highest contrast and focal quality. Results: For all reconstructions, the location of the synthetic tumors in the experimental setup was consistent with the position in the both the monostatic and multistatic reconstructed images. The average spatial error was less than 4 mm, which is half the spatial resolution of the data acquisition system. The average SCR, CCR, and TFRR of the images reconstructed with the multistatic approach were 15.0, 9.4, and 10.0 dB, respectively. In comparison, monostatic images obtained using the datasets from the same experimental setups yielded average SCR, CCR, and TFRR values of 12.8, 4.9, and 5.9 dB. No artifacts, defined as responses generated by the reconstruction method of at least half the energy of the tumor signatures, were noted in the multistatic reconstructions. The average execution time of the images formed using the proposed approach was 4 s, which is one order of magnitude faster than the current state‐of‐the‐art time‐domain multistatic breast microwave radar reconstruction algorithms. Conclusions: The images generated by the proposed method show that multistatic holography is capable of forming spatially accurate images in real‐time with signal to clutter levels and contrast values higher than other published monostatic and multistatic cylindrical radar reconstruction approaches. In comparison to the monostatic holographic approach, the images generated by the proposed multistatic approach had SCR values that were at least 50% higher. The multistatic images had CCR and TFRR values at least 200% greater than those formed using a monostatic approach.